Determination of N for Heaviest and Lightest Isotopes of Each Z≥92 Elements for producting - صقر, هشام; عباس, مفيد; محمد فاهود; بهجت ابراهيم (Latakia University Journal -Basic Sciences Series, 2023)
In nature, there are less than 300 natural isotopes. Their high proton numbers are Z=92. Conversely, there are more than 5000 artificial isotopes which are being produced in the reactors and accelerators or by chemical method. The maximum of artificial Z has transcended the value Z=130, so , day after day the number of artificial isotopes which are produced by human has increased, along with development of equipment and method which are being used, especially of increasing the accelerating energies in the accelerators. Nowadays, artificial isotopes of the elements existed naturally or artificially produced of N values (number of neutrons) are being produced. Thus, by decreasing the minimum and increasing the maximum with the development time progresses. Certain conditions must be achieved in order to have naturally existed nuclei or artificially being produced. Some of these conditions are as followers: Binding Energy for any of its protons or neutron in any part of the nucleus is bigger than zero. Noting that, scheduling always reaches the neutron existed on the nucleus surface and also the proton, the nearest to its surface. Average Binding Energy .decreases as N increases by stability of Z (for each element) . Besides with the increase of Z by stability of N ( for each group of Isotones). In this research, we try to find opposite of the lightest isotop and the heaviest isotope in order which can be produced for each element, i.e for each value of Z. The research was limited to study the elements because of its specifi feature distinguished it from others, that is , it is sub missed to simple laws such as linear relations for each of with N in each element.